2010
DOI: 10.1111/j.1360-0443.2010.03077.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated overdose mortality rates among First Nations individuals in a Canadian setting: a population‐based analysis

Abstract: This report found highly elevated overdose death rates and levels of premature mortality among First Nations Canadians in British Columbia compared to the general population. While previously unidentified, these findings are consistent with the poorer population health profile of First Nations Canadians. Although further research is needed to identify the causes of the elevated death rates, our findings support increased availability of evidence-based overdose prevention measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 40 publications
(42 reference statements)
0
29
0
Order By: Relevance
“…A future study might purposively sample pharmacies in areas or communities where rates of opioid prescribing, opioid-related overdose, visits to the emergency department and death are disproportionately higher than in others. 7,14,40,48 …”
Section: Limitationsmentioning
confidence: 99%
“…A future study might purposively sample pharmacies in areas or communities where rates of opioid prescribing, opioid-related overdose, visits to the emergency department and death are disproportionately higher than in others. 7,14,40,48 …”
Section: Limitationsmentioning
confidence: 99%
“…Also, the high rates of death of HIV/AIDS patients could be a direct result of drug overdose. A review of coroner's files for deaths between 2001 and 2005 found highly elevated overdose death rates and levels of premature mortality among First Nations people in BC compared to the general population (Milloy et al, 2010).…”
Section: Alcohol and Drug Addictionmentioning
confidence: 99%
“…However, sex was not significantly associated with mortality in our final model, which may show that sex per se is not biologically associated with mortality but rather that HCV, suicide and fatal overdose are highly gendered among Indige nous people, as previously highlighted by the Cedar Project and others. 27,[37][38][39] It is essential that young Indigenous women who use drugs are meaningfully involved in the development of pro grams to support their health and wellbeing, reduce drug related harms and remove barriers to care.…”
Section: Discussionmentioning
confidence: 99%